The Dawkins delusion : atheist fundamentalism and the denial of the divine - McGrath, Alister E., 1953-; McGrath, Joanna Collicutt (Downers Grove, Ill. : InterVarsity Press, 2007)
"Alister McGrath is ideally placed to evaluate Dawkins' ideas. Once an atheist himself, he gained a doctorate in molecular biophysics before going on to become a leading Christian theologian. He wonders how two people, who have reflected at length on substantially the same world, could possibly have come to such different conclusions about God. McGrath subjects Dawkins' critique of faith to rigorous scrutiny. This book will be warmly received by those looking for a reliable assessment of The God Delusion and the many questions it raises - including, above all, the relevance of faith and the quest for meaning."--Jacket.
Deluded about God? -- Has science disproved God? -- What are the origins of religion? -- Is religion evil?
Includes bibliographical references (p. [111]-115) and index.
Keywords: Dawkins, Richard, -- 1941-; Christianity and atheism; Apologetics